Sexual Harassment Experiences and Its Mental Health Consequences among Female Undergraduates: A Case of Alex Ekwueme Federal University, Nigeria - Otu Esther Orieoma; Aniwada Elias Chikee (Archives of Current Research International, 2025)
Introduction: Sexual harassment is described as unwanted sexual advances, forceful requests for sexual favors, and other verbal or physical conducts of a sexual nature. It is a global threat. This study assessed the sexual harassment knowledge, experiences, factors and its mental health consequences among female undergraduates of Alex Ekwueme Federal University Ndufu Alike Ikwo Ebonyi State, Nigeria. Methods: A descriptive cross sectional study design was done using semi-structured questionnaires. Multistage sampling was used in selection of 400 students that gave consent for the study. Ethical consideration was dully observed. Analysis were done using the IBM SPSS version 25. The data were presented in tables. Chi square test was used to ascertain association between socio-demographic factors and experience of sexual harassments at significant level of p < 0.05 Results: A total of 397 (99.3%) students have heard of sexual harassment. Commonest sources of information were Mass media 329 (82.3%) and social media 328 (82.0%). Majority 260 (65%) have been sexually harassed especially by their casual partners (e.g male friends) and 90 (29.5%) by their lecturers 79 (24.6%). Most sexual harassment 134 (42.5%) occurred during visit to perpetrator with 97 (30.8%) out of violence/force and 69 (21.7%) in course of seeking favour. Common forms of harassment encountered include; 282 (88.1%) deliberate touching and cornering, 269 (82.8%) fondling/grabbing of sensitive body part and 270 (81.8%) actual/attempted rape. Significant Mental health effect include; worries 153 (48.4%), frightened or nervous 77 (24.3%), thought disorder and delusions 71 (22.5%) and phobia 64 (20.3%). There was statistically significant association for marital status for what (χ2 = 16.987, p < 0.001) though not a predictor. Conclusion: Sexual harassment was high among the female students with residual mental health consequences. It portends danger and should not be trivialized nor dismissed as it emboldens the perpetrators. All stakeholders should lend effort and support to tame this ugly tide.